Rola niewerbalnych form powitania w kształtowaniu kompetencji komunikatywnej i interkulturowej w aspekcie glottodydaktycznym - Pietrus-Rajman, Marianna Agnieszka (Aspects of Communicative and Intercultural Competence in Foreign Language Teaching, 2008)
The paper presents non-verbal communication as an important constituent of communicative and intercultural competence, that should be addressed in modern language teaching practice. Requirements of glottodydactics over recent decades are also discussed, with special attention to non-verbal forms of communication. Routines and rituals of everyday life are discussed, in particular the routine greeting forms, factors that influence them and basic characteristics of such forms of communication.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 114-123